PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN UMKM (Studi pada CV. Kanthi Harum Surabaya) - Agata Rahmi Pertiwi; Dimas Hendrawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the effect of Relationship Marketing Variables (trust, commitment, and communication) on Loyalty at Small Business Customers (Study at CV Kanthi Harum Surabaya). This study uses an explanatory method which aims to knowing the causal relationship between the dependent and independent variables through the parsial and simultaneous hypothesis testing. The sampling technique used was probability sampling with slovin’s formula and obtained 110 companies as the samples from 150 companies that already exist on the object’s database. Regression analysis showed that Relationship Marketing variables (trust, commitment, and communication) have a significant influence on customer loyalty. The simultaneous and partial hypothesis testing showed that the independent variables influence the dependent variable. The correlation coefficient shows that the correlation between the dependent and independent variables are positive and strong. Keywords: Trust, Commitment, Communication, Relationship Marketing, Loyalty.